Resin composition as well as preparation method and application thereof
By using a composition of fluorine-containing resin, modified filler and unmodified inorganic filler in the circuit substrate, the thermal stress concentration problem caused by the difference in thermal expansion coefficient between the resin and the filler is solved, and the thermal stress buffering effect of the circuit substrate is achieved to avoid division Layer and explosive plate phenomenon and maintain good dielectric and heat dissipation performance.
Patent Information
- Application Number
- CN202411319465.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-31
AI Technical Summary
The difference in thermal expansion coefficient between fluorine-containing resin and inorganic filler leads to concentrated thermal stress of circuit substrates, resulting in layering and explosive plates.
Using a composition of fluorine-containing resin, modified filler and unmodified inorganic filler, the modified filler is wound with the fluorine-containing resin through grafting organic segments or forming a conjugated structure to reduce thermal stress, and disperse heat stress through the inorganic filler body. , reduce porosity and improve density.
Effectively improve the buffering thermal stress effect of the circuit substrate, prevent layering and explosive plates, while maintaining dielectric and heat dissipation performance, and extending service life.
Smart Images

Figure BDA0005053661810000131 
Figure BDA0005053661810000141
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electronic industry, and in particular to a resin composition and a preparation method and application thereof. Background Art
[0002] Fluorine-containing resin has good dielectric properties and has great application potential in electronic components such as circuit substrates. At present, higher requirements are put forward for the dielectric properties and heat dissipation properties of circuit substrates, which requires increasing the types and addition amounts of inorganic fillers in the resin composition. However, at room temperature, the thermal expansion coefficients of fluorine-containing resins and inorganic fillers differ greatly, resulting in concentrated thermal stress in the circuit substrate, which causes delamination and explosion of the circuit substrate. Summary of the invention
[0003] Based on this, it is necessary to provide a resin composition and its preparation method and application to address the above problems. The resin composition provided by the present invention takes into account both dielectric properties and heat dissipation properties, and has an excellent effect of buffering thermal stress, effectively avoiding delamination and explosion of the prepared circuit substrate, and has broad application prospects.
[0004] A resin composition comprising a fluorine-containing resin, a modified filler and an unmodified inorganic filler;
[0005] The modified filler comprises an inorganic filler body and an organic chain segment grafted on the surface of the inorganic filler body, wherein the organic chain segment comprises a saturated alkane main chain, the carbon number of the saturated alkane main chain is ≥12 and / or the side chain of the organic chain segment contains a carbonyl functional group.
[0006] In one embodiment, the median particle size D of the modified filler is 50 1.5μm~6μm;
[0007] And / or, the median particle size D of the modified filler 50 Smaller than the median particle size D of the unmodified inorganic filler 50 ;
[0008] And / or, the CTE of the modified filler is ≤5ppm / °C;
[0009] And / or, the grafting rate of the modified filler is 30% to 40%.
[0010] In one embodiment, the median particle size D of the inorganic filler body is 50 1μm~5μm;
[0011] And / or, the CTE of the inorganic filler body is ≤5ppm / °C;
[0012] And / or, the inorganic filler body is selected from spherical fillers;
[0013] And / or, the inorganic filler body is selected from at least one of silicon oxide, silicon nitride and aluminum oxide.
[0014] In one embodiment, the saturated alkane main chain is used as a symmetry axis, and the side chain containing the carbonyl functional group is symmetrical.
[0015] In one embodiment, the organic segment is formed by grafting a heterochain polymer, and the heterochain polymer is selected from one of 1-amino-3,3-diacetyl-dodecane, 1-amino-5,5-diacetyl-pentadecane, 1-carboxy-5,5-diacetyl-pentadecane, 1-amino-5,6-diacetyl-dodecane, 1-amino-3,3-diacetyl-octane and 1-amino-dodecane.
[0016] In one embodiment, the number average molecular weight of the fluorine-containing resin is ≥500,000, and the molecular weight distribution is between 1.05 and 1.2;
[0017] And / or, the fluorine-containing resin is at least one selected from polytetrafluoroethylene resin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer and tetrafluoroethylene-hexafluoropropylene copolymer.
[0018] In one embodiment, the unmodified inorganic filler is selected from one of boron nitride, aluminum oxide, silicon nitride and aluminum nitride;
[0019] And / or, the mass fraction of the unmodified inorganic filler in the resin composition is greater than the mass fraction of the modified filler in the resin composition.
[0020] In one embodiment, the resin composition includes 30 to 50 parts by weight of a fluorine-containing resin, 10 to 20 parts by weight of a modified filler, and 40 to 60 parts by weight of an unmodified inorganic filler.
[0021] A prepreg made from the resin composition as described above.
[0022] A circuit substrate made of the prepreg as described above.
[0023] A printed circuit board made of the circuit substrate as described above.
[0024] The above-mentioned resin composition includes a fluorine-containing resin, an unmodified inorganic filler and a modified filler with a specific structure. The modified filler forms a nano-confined phase in the resin composition. On the one hand, the saturated alkane main chain grafted on the surface of the modified filler is entangled with the fluorine-containing resin molecular chain, or a conjugated structure is formed with the fluorine-containing resin through the carbonyl functional group of the branch chain, which is beneficial to reduce thermal stress, reduce the shrinkage of the fluorine-containing resin, and reduce the difference in thermal expansion coefficient between the fluorine-containing resin and the unmodified inorganic filler, which is beneficial to avoid delamination and bursting of the prepared circuit substrate; on the other hand, the inorganic filler body promotes the dispersion of thermal stress, effectively reduces the porosity of the circuit substrate, and improves the density of the circuit substrate, which is beneficial to avoid delamination and bursting of the circuit substrate.
[0025] Therefore, the resin composition of the present invention can effectively improve the thermal stress buffering effect of the circuit substrate while ensuring the dielectric properties and heat dissipation properties of the circuit substrate, prevent the circuit substrate from delamination and explosion, and is beneficial to increasing the service life of the circuit substrate, and has broad application prospects. DETAILED DESCRIPTION
[0026] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0027] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.
[0028] The resin composition provided by the present invention comprises a fluorine-containing resin, a modified filler and an unmodified inorganic filler; the modified filler comprises an inorganic filler body and an organic chain segment grafted on the surface of the inorganic filler body, the organic chain segment comprises a saturated alkane main chain, the carbon number of the saturated alkane main chain is ≥12 and / or the side chain of the organic chain segment contains a carbonyl functional group.
[0029] The above-mentioned resin composition includes a fluorine-containing resin, an unmodified inorganic filler and a modified filler with a specific structure. The modified filler forms a nano-confined phase in the resin composition. On the one hand, the long molecular chain of the saturated alkane main chain grafted on the surface of the modified filler can be physically entangled with the fluorine-containing resin molecular chain, which is beneficial to reducing the thermal stress of the prepared circuit substrate. At the same time, the long molecular chain is beneficial to increasing the transmission distance of thermal stress and improving the thermal stress dispersion effect, thereby helping to reduce the shrinkage of the fluorine-containing resin and reduce the difference in thermal expansion coefficient between the fluorine-containing resin and the unmodified inorganic filler, thereby avoiding delamination and bursting of the circuit substrate; or, when the side chain of the saturated alkane main chain contains a carbonyl functional group, the carbon atom part of the carbonyl functional group carries a certain positive charge and can interact with the fluorine atoms with strong electronegativity in the fluorine-containing resin, so that a conjugated structure is formed between the saturated alkane main chain and the fluorine-containing resin, thereby further inhibiting the shrinkage of the fluorine-containing resin and reducing the difference in thermal expansion coefficient between the fluorine-containing resin and the unmodified inorganic filler, thereby avoiding delamination and bursting of the circuit substrate.
[0030] On the other hand, the inorganic filler body has a good effect of dispersing thermal stress, while effectively reducing the porosity of the circuit substrate and improving the density of the circuit substrate, which is beneficial to avoid delamination and bursting of the circuit substrate.
[0031] In addition, the unmodified inorganic filler has good heat dissipation performance, which is beneficial to ensure the heat dissipation performance of the circuit substrate.
[0032] Therefore, under the combined action of the modified filler with a specific structure and the fluorine-containing resin and the unmodified inorganic filler, the above-mentioned resin composition can effectively improve the effect of the circuit substrate in buffering thermal stress while ensuring the dielectric properties and heat dissipation properties of the circuit substrate, prevent the circuit substrate from delamination and bursting, and is beneficial to improving the service life of the circuit substrate, and has broad application prospects.
[0033] In one embodiment, the median particle size D of the modified filler is 50 Smaller than the median particle size D of the unmodified inorganic filler 50 , which is conducive to dispersing the modified filler in the gaps between the unmodified inorganic fillers, improving the dispersibility of the modified filler, promoting the formation of more thermal stress release points, avoiding local thermal stress concentration leading to delamination and explosion of the circuit substrate, and is conducive to improving the dielectric properties of the circuit substrate.
[0034] Preferably, the median particle size D of the modified filler is 50 The diameter of the modified filler is 1.5 μm to 6 μm, which is beneficial to improving the dispersibility of the modified filler in the resin composition, thereby improving the buffering effect of the prepared circuit substrate on thermal stress, avoiding delamination and explosion of the circuit substrate, and is beneficial to improving the service life of the circuit substrate.
[0035] In one embodiment, the CTE of the modified filler is ≤5 ppm / °C, which is beneficial to improving the ability of the modified filler to withstand thermal stress and to improving the thermal stress dispersion effect, thereby improving the buffering effect of the prepared circuit substrate on thermal stress.
[0036] In order to further reduce the thermal stress in the circuit substrate, improve the dispersion effect of the thermal stress, improve the density of the circuit substrate, and improve the dielectric properties of the circuit substrate, the grafting rate of the modified filler is preferably 30% to 40%.
[0037] It should be noted that the above grafting rate is expressed as the mass ratio of the organic segment to the inorganic filler body in the modified filler.
[0038] In order to further improve the dispersibility of the modified filler in the resin composition, thereby improving the buffering effect of the prepared circuit substrate on thermal stress, and further reducing the porosity of the circuit substrate, improving the density of the circuit substrate, and improving the dielectric properties of the circuit substrate, thereby avoiding the delamination and explosion of the circuit substrate, the median particle size D of the inorganic filler body is 50 It is preferably 1 μm to 5 μm.
[0039] In one embodiment, the CTE of the inorganic filler body is ≤5ppm / °C, which is beneficial to improving the ability of the inorganic filler body to withstand thermal stress, thereby improving the ability of the modified filler to transmit and disperse thermal stress, and improving the buffering effect of the prepared circuit substrate on thermal stress.
[0040] Preferably, the inorganic filler body is selected from spherical fillers. The isotropic spherical morphology is conducive to the modified filler to transmit and disperse thermal stress in multiple directions, thereby improving the transmission effect of thermal stress between the modified filler grains. At the same time, it is conducive to reducing the porosity of the circuit substrate, improving the density of the circuit substrate, and thus avoiding stratification and bursting of the circuit substrate.
[0041] Specifically, the inorganic filler body is selected from at least one of silicon oxide, silicon nitride and aluminum oxide.
[0042] Preferably, the saturated alkane main chain is used as the symmetry axis, and the side chain containing the carbonyl functional group is symmetrical, which is beneficial to reducing the polarity of the saturated alkane main chain, thereby reducing the concentration of thermal stress in the saturated alkane main chain, further improving the dispersion effect of thermal stress, and avoiding delamination and explosion of the circuit substrate.
[0043] It should be noted that the symmetry of the above-mentioned branches is represented by the presence of two branches with the same structure on the same carbon atom in the saturated alkane main chain, and both branches contain carbonyl functional groups; it can be understood that the number of the carbonyl functional groups is an even number, and the present invention has no special restrictions on the number of branches of the organic chain segment and the number of connected carbonyl functional groups, and the number of carbonyl functional groups can be 2, 4 or 6, etc.
[0044] In one embodiment, the organic segment is formed by grafting a heterochain polymer, and the heterochain polymer is selected from one of 1-amino-3,3-diacetyl-dodecane, 1-amino-5,5-diacetyl-pentadecane, 1-carboxy-5,5-diacetyl-pentadecane, 1-amino-5,6-diacetyl-dodecane, 1-amino-3,3-diacetyl-octane and 1-amino-dodecane.
[0045] It can be understood that the heterochain polymer contains active groups that can react with hydroxyl groups on the surface of the inorganic filler body, such as amino groups and carboxyl groups, so as to achieve the grafting of organic chain segments onto the surface of the inorganic filler body.
[0046] In one embodiment, the number average molecular weight of the fluorine-containing resin is ≥500000, and the molecular weight distribution is between 1.05 and 1.2. On the one hand, the number average molecular weight of the fluorine-containing resin is relatively large, which is beneficial to improving the interaction and entanglement between the fluorine-containing resin molecular chains and between the fluorine-containing resin molecular chains and the saturated alkane main chain molecular chains, further improving the ability of the fluorine-containing resin to resist thermal stress, and is beneficial to reducing the shrinkage and cracking of the fluorine-containing resin in the circuit substrate and reducing the difference in thermal expansion coefficient between the fluorine-containing resin and the unmodified inorganic filler. On the other hand, the number average molecular weight distribution range of the fluorine-containing resin is relatively narrow and the low molecular weight component is small, which is beneficial to avoid local thermal stress concentration, and further helps to avoid delamination and bursting of the circuit substrate.
[0047] It can be understood that the above molecular weight distribution is expressed as the ratio of the number average molecular weight to the weight average molecular weight of the fluorine-containing resin. The closer the molecular weight distribution is to 1, the narrower the molecular weight distribution range of the fluorine-containing resin.
[0048] Specifically, the fluorine-containing resin is at least one selected from polytetrafluoroethylene resin (PTFE resin), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA resin) and tetrafluoroethylene-hexafluoropropylene copolymer (FEP resin).
[0049] It can be understood that the present invention has no special restrictions on the type of unmodified inorganic filler, and conventional inorganic fillers in the art can be used, which is beneficial to improving the heat dissipation of the prepared circuit substrate. For example, the unmodified inorganic filler of the present invention is selected from at least one of boron nitride, aluminum oxide, silicon nitride, and aluminum nitride; at the same time, the present invention has no special restrictions on the morphology of the unmodified inorganic filler, such as flake, angular, etc.
[0050] It should be noted that the inorganic filler main body and the unmodified inorganic filler of the present invention may be of the same type or different types.
[0051] In one embodiment, the mass fraction of the unmodified inorganic filler in the resin composition is greater than the mass fraction of the modified filler in the resin composition.
[0052] Specifically, the resin composition includes 30 to 50 parts by weight of a fluorine-containing resin, 10 to 20 parts by weight of a modified filler, and 40 to 60 parts by weight of an unmodified inorganic filler, which is beneficial to improving the effect of buffering thermal stress of the circuit substrate, preventing delamination and bursting of the circuit substrate, and improving the service life of the circuit substrate. At the same time, it avoids agglomeration of the modified filler in the resin composition, which is beneficial to ensuring and improving the dielectric properties and heat dissipation properties of the circuit substrate, and has broad application prospects.
[0053] It can be understood that the weight parts of the above fluorine-containing resin are expressed as the weight parts of the fluorine-containing resin without solvent, that is, in the suspension of the fluorine-containing resin, the weight parts of the above fluorine-containing resin = the weight parts of the suspension × solid content.
[0054] It should be noted that the resin composition may also include auxiliary agents such as coupling agents, thickeners, and dispersants. The present invention has no special restrictions on this. Those skilled in the art can choose whether to add and the amount of addition according to actual needs; the above-mentioned coupling agents, thickeners, dispersants, etc. are all commonly used auxiliary agents in the field, and the present invention has no special restrictions on their types.
[0055] The present invention also provides a prepreg made from the resin composition as described above.
[0056] It should be noted that the prepreg in the present invention can be prepared by an existing method, and the present invention does not limit this. Preferably, after the above resin composition is mixed evenly, it is impregnated or coated on the reinforcing material, and dried in an oven at 120°C to 180°C for 1.5min to 6min to obtain a prepreg, and the reinforcing material is preferably at least one of glass fiber cloth, aramid cloth and carbon fiber cloth.
[0057] The present invention also provides a circuit substrate made of the prepreg as described above, which has good dielectric properties and heat dissipation properties, and at the same time has a good effect of buffering thermal stress. The circuit substrate is not prone to delamination and board explosion, has a long service life, and has broad application prospects.
[0058] Specifically, the circuit substrate includes an insulating layer and a conductive layer arranged on at least one surface of the insulating layer, wherein the insulating layer is pressed from one or more superimposed semi-cured sheets as described above, and the conductive layer is selected from conductive materials such as copper foil and aluminum foil, and the present invention does not limit this.
[0059] The present invention also provides a printed circuit board made of the circuit substrate as described above, which can meet the needs of more usage scenarios and has high market application potential.
[0060] Specifically, the printed circuit board is made of the circuit substrate through processes such as drilling, hole filling, micro-etching, pre-preg, activation, acceleration, chemical copper and copper thickening.
[0061] Hereinafter, the resin composition and its preparation method and application will be further described through the following specific examples.
[0062] Example 1
[0063] 60 parts by weight of silicon dioxide (spherical, D 50 3μm, CTE 4ppm / ℃) and 100 parts by weight of butanone were stirred and mixed at 550rpm, and then 40 parts by weight of 1-amino-5,5-diacetyl-pentadecane were added and stirred for reaction. The reaction temperature was 70℃ and the reaction time was 24h. The modified filler (D 50 The surface of the saturated alkane has a carbon chain length of 15 and contains carbonyl groups on the side chains, and the grafting rate is 36%).
[0064] 33.1 parts by weight of boron nitride (D 50 13 μm) and 0.36 parts by weight of polyethylene glycol monooctylphenyl ether were mixed in deionized water and uniformly dispersed at 1000 r / min for 30 min, and then 22.1 parts by weight of aluminum oxide (D 50 12 μm) was stirred at high speed again, and after stirring evenly, 15 parts by weight of modified filler and 66 parts by weight of polytetrafluoroethylene suspension (manufacturer Juhua, solid content 60%, number average molecular weight 550000, molecular weight distribution 1.1) were added and stirred at low speed of 300 r / min for 30 min to obtain a resin composition.
[0065] Example 2
[0066] 60 parts by weight of silicon nitride (spherical, D 50 1.5 μm, CTE 5 ppm / ℃) and 100 parts by weight of butanone were stirred and mixed at 550 rpm, and then 40 parts by weight of 1-carboxyl-5,5-diacetyl-pentadecane were added and stirred for reaction. The reaction temperature was 70℃ and the reaction time was 24h. The modified filler (D 50 The surface of the saturated alkane has a carbon chain length of 15 and contains carbonyl groups on the branch chain, and the grafting rate is 31%).
[0067] 42 parts by weight of boron nitride (D 50 13 μm) and 0.36 weight parts of polyethylene glycol monooctylphenyl ether were mixed in deionized water and uniformly dispersed at a high speed of 1000 r / min for 30 min, and then 10 weight parts of modified filler and 83 weight parts of tetrafluoroethylene-hexafluoropropylene copolymer suspension (manufacturer Juhua, solid content of 60%, number average molecular weight of 500000, molecular weight distribution of 1.06) were added and stirred at a low speed of 300 r / min for 30 min to obtain a resin composition.
[0068] Example 3
[0069] 60 parts by weight of silicon dioxide (spherical, D 50 5 μm, CTE 4 ppm / ℃) and 100 parts by weight of butanone were stirred and mixed at 550 rpm, and then 40 parts by weight of 1-amino-3,3-diacetyl-dodecane were added and stirred for reaction. The reaction temperature was 70℃ and the reaction time was 24h. The modified filler (D 50 The surface of the saturated alkane has a carbon chain length of 12 and contains carbonyl groups on the side chains, and the grafting rate is 40%).
[0070] 38.1 parts by weight of silicon nitride (D 50 8μm) and 0.36 parts by weight of polyethylene glycol monooctylphenyl ether were mixed in deionized water and uniformly dispersed at 1000r / min for 30min, and then 22.1 parts by weight of aluminum nitride (D 50 The mixture was stirred at a high speed again, and after being stirred evenly, 20 parts by weight of modified filler and 50 parts by weight of polytetrafluoroethylene suspension (manufacturer Juhua, with a solid content of 60%, a number average molecular weight of 800000, and a molecular weight distribution of 1.1) were added, and stirred at a low speed of 300 r / min for 30 min to obtain a resin composition.
[0071] Example 4
[0072] The difference between Example 4 and Example 1 is that 1-amino-5,6-diacetyl-dodecane is used to replace 1-amino-5,5-diacetyl-pentadecane, and in the obtained modified filler, D 50 The surface of the nanostructured carbon fiber is 3.3 μm, the CTE is 4 ppm / °C, the carbon chain length of the saturated alkane grafted on the surface is 12 and the branch chain contains a carbonyl group, and the grafting rate is 35%.
[0073] Example 5
[0074] The difference between Example 5 and Example 1 is that the silicon dioxide used is spherical, D 50 8μm, CTE 4ppm / ℃, D 50 The carbon chain length of the saturated alkane grafted on the surface is 15 and contains carbonyl groups on the side chains, and the grafting rate is 36%; the inorganic filler used in preparing the resin composition is 33.1 parts by weight of boron nitride (D 50 8 μm) and 22.1 parts by weight of aluminum oxide (D 50 is 5μm).
[0075] Example 6
[0076] The difference between Example 6 and Example 1 is that the silicon dioxide used is spherical, D 50 The modified filler has a density of 3.5 μm and a CTE of 13 ppm / ℃. 50 The surface of the nanostructured carbon fiber is 4 μm, the CTE is 14 ppm / °C, the carbon chain length of the saturated alkane grafted on the surface is 15 and the branch chain contains a carbonyl group, and the grafting rate is 33%.
[0077] Example 7
[0078] The difference between Example 7 and Example 1 is that 54 parts by weight of 1-carboxy-5,5-diacetyl-pentadecane is added, and the grafting rate of the obtained modified filler is 45%.
[0079] Example 8
[0080] The difference between Example 8 and Example 1 is that 1-amino-3,3-diacetyl-octane is used instead of 1-amino-5,5-diacetyl-pentadecane, and in the prepared modified filler, D 50 The surface of the nanostructured carbon fiber is 3.3 μm, the CTE is 4 ppm / °C, the carbon chain length of the saturated alkane grafted on the surface is 8 and the branch chain contains a carbonyl group, and the grafting rate is 33%.
[0081] Example 9
[0082] The difference between Example 9 and Example 1 is that 1-amino-dodecane is used instead of 1-amino-5,5-diacetyl-pentadecane, and in the obtained modified filler, D50 The carbon chain length of the saturated alkane grafted on the surface is 12 and there is no carbonyl group on the branch chain. The grafting rate is 35%.
[0083] Comparative Example 1
[0084] The difference between Comparative Example 1 and Example 1 is that 33.1 parts by weight of boron nitride (D 50 13 μm) and 0.36 parts by weight of polyethylene glycol monooctylphenyl ether were mixed in deionized water and uniformly dispersed at a high speed of 1000 r / min for 30 min, and then 9.5 parts by weight of silicon dioxide, 5.5 parts by weight of 1-amino-5,5-diacetyl-pentadecane and 66 parts by weight of polytetrafluoroethylene suspension (manufacturer Juhua, solid content of 60%, number average molecular weight of 550000, molecular weight distribution of 1.1) were added and stirred at a low speed of 300 r / min for 30 min to obtain a resin composition.
[0085] Comparative Example 2
[0086] The difference between Comparative Example 2 and Example 1 is that 33.1 parts by weight of boron nitride (D 50 13 μm) and 0.36 weight parts of polyethylene glycol monooctylphenyl ether were mixed in deionized water and uniformly dispersed at a high speed of 1000 r / min for 30 min, and then 15 weight parts of silicon dioxide and 66 weight parts of polytetrafluoroethylene suspension (manufacturer Juhua, solid content of 60%, number average molecular weight of 550000, molecular weight distribution of 1.1) were added and stirred at a low speed of 300 r / min for 30 min to obtain a resin composition.
[0087] Comparative Example 3
[0088] The difference between Comparative Example 3 and Example 1 is that 33.1 parts by weight of boron nitride (D 50 13 μm) and 0.36 parts by weight of polyethylene glycol monooctylphenyl ether were mixed in deionized water and uniformly dispersed at a high speed of 1000 r / min for 30 min, and then 15 parts by weight of 1-amino-5,5-diacetyl-pentadecane and 66 parts by weight of polytetrafluoroethylene suspension (manufacturer Juhua, solid content of 60%, number average molecular weight of 550000, molecular weight distribution of 1.1) were added and stirred at a low speed of 300 r / min for 30 min to obtain a resin composition.
[0089] Comparative Example 4
[0090] The difference between Comparative Example 4 and Example 1 is that 30 parts by weight of silicon dioxide (spherical, D 503μm, CTE 4ppm / ℃) and 60 parts by weight of butanone were stirred and mixed at 550rpm, and then 60 parts by weight of 1-amino-octane were added and continued to stir and react. The reaction temperature was 70℃ and the reaction time was 24h. The modified filler (D 50 The surface of the saturated alkane has a carbon chain length of 8 and no carbonyl group on the branch chain, and the grafting rate is 33%).
[0091] Comparative Example 5
[0092] 60 parts by weight of silicon dioxide (spherical, D 50 3μm, CTE 4ppm / ℃) and 100 parts by weight of butanone were stirred and mixed at 550rpm, and then 25 parts by weight of 1-amino-5,5-diacetyl-pentadecane were added and stirred for reaction. The reaction temperature was 70℃ and the reaction time was 24h. The modified filler (D 50 The surface of the saturated alkane has a carbon chain length of 15 and contains carbonyl groups on the side chains, and the grafting rate is 36%).
[0093] 0.36 parts by weight of polyethylene glycol monooctylphenyl ether, 15 parts by weight of modified filler and 66 parts by weight of polytetrafluoroethylene suspension (manufacturer Juhua, solid content 60%, number average molecular weight 550000, molecular weight distribution 1.1) were stirred at a low speed of 300 r / min for 30 minutes to obtain a resin composition.
[0094] Application Examples
[0095] The resin compositions prepared in all the examples and comparative examples were uniformly coated on the glass fiber cloth and dried at 110°C for 5 min. After drying, they were sintered at 382°C for 5 min to obtain a prepreg. Four prepregs were stacked, and copper foil was covered on the upper and lower sides thereof. The prepregs were placed in a high temperature press at a temperature of 220°C and a pressure of 25 kg / cm 2 The reaction mixture was cured for 3 hours to obtain a circuit substrate.
[0096] The circuit substrates prepared in all application examples and application comparison examples were subjected to performance tests, and the test indicators and methods were as follows:
[0097] (1) Delamination and board explosion: The circuit substrate is gradually heated to a fixed temperature of 288°C using the TMA method (static thermal mechanical analysis) to test the thermal delamination time of the circuit substrate in the Z axis;
[0098] (2) Dielectric loss factor (Df): tested using the SPDR (splite post dielectric resonator) method at 10 GHz.
[0099] (3) Heat dissipation performance: Thermal conductivity is tested according to ASTM-D5470.
[0100] The performance test results of the circuit substrates prepared in all the application examples and application comparison examples are shown in Table 1.
[0101] Table 1
[0102]
[0103]
[0104] According to the test results of Table 1, the thermal stratification time of the circuit substrates obtained by all application embodiments is relatively long, and they have a lower dielectric loss factor and a higher thermal conductivity, while the thermal stratification time of the circuit substrates obtained by all application comparison examples is significantly shorter, and the dielectric loss factor is higher and the thermal conductivity is lower. Therefore, the resin composition of the present invention effectively improves the effect of buffering thermal stress of the circuit substrate while ensuring the dielectric properties and heat dissipation performance of the circuit substrate, prevents the circuit substrate from stratification and explosion, is conducive to improving the service life of the circuit substrate, and has a wide range of application prospects.
[0105] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A resin composition, characterized in that The resin composition comprises a fluorine-containing resin, a modified filler and an unmodified inorganic filler; The modified filler comprises an inorganic filler body and an organic chain segment grafted on the surface of the inorganic filler body, wherein the organic chain segment comprises a saturated alkane main chain, the carbon number of the saturated alkane main chain is ≥12 and / or the side chain of the organic chain segment contains a carbonyl functional group.
2. The resin composition according to claim 1, characterized in that The median particle size D of the modified filler 50 1.5μm~6μm; And / or, the median particle size D of the modified filler 50 Smaller than the median particle size D of the unmodified inorganic filler 50 ; And / or, the CTE of the modified filler is ≤5ppm / °C; And / or, the grafting rate of the modified filler is 30% to 40%.
3. The resin composition according to claim 1, characterized in that The median particle size D of the inorganic filler body 50 1μm~5μm; And / or, the CTE of the inorganic filler body is ≤5ppm / °C; And / or, the inorganic filler body is selected from spherical fillers; And / or, the inorganic filler body is selected from at least one of silicon oxide, silicon nitride and aluminum oxide.
4. The resin composition according to claim 1, characterized in that With the saturated alkane main chain as the symmetry axis, the side chain containing the carbonyl functional group has symmetry.
5. The resin composition according to claim 1, characterized in that The organic chain segment is formed by grafting a heterochain polymer, and the heterochain polymer is selected from at least one of 1-amino-3,3-diacetyl-dodecane, 1-amino-5,5-diacetyl-pentadecane, 1-carboxyl-5,5-diacetyl-pentadecane, 1-amino-5,6-diacetyl-dodecane, 1-amino-3,3-diacetyl-octane and 1-amino-dodecane.
6. The resin composition according to claim 1, characterized in that The number average molecular weight of the fluorine-containing resin is ≥500,000, and the molecular weight distribution is between 1.05 and 1.2; And / or, the fluorine-containing resin is at least one selected from polytetrafluoroethylene resin, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer and tetrafluoroethylene-hexafluoropropylene copolymer.
7. The resin composition according to claim 1, characterized in that The unmodified inorganic filler is selected from at least one of boron nitride, aluminum oxide, silicon nitride and aluminum nitride; And / or, the mass fraction of the unmodified inorganic filler in the resin composition is greater than the mass fraction of the modified filler in the resin composition.
8. The resin composition according to claim 1 or 7, characterized in that The resin composition comprises 30 to 50 parts by weight of a fluorine-containing resin, 10 to 20 parts by weight of a modified filler and 40 to 60 parts by weight of an unmodified inorganic filler.
9. A prepreg made from the resin composition according to any one of claims 1 to 8.
10. A circuit substrate made of the prepreg as claimed in claim 9.
11. A printed circuit board made using the circuit substrate as claimed in claim 10.
